The ethics of public work and the impertinence of managerialism as a model of work organization in times of crisis - Sisto, Vicente; Ramírez Casas Del Valle, Lorena Pía.; Núñez Parra, Lorena.; López Barraza, Andrea. (Pontificia Universidad Católica de Valparaíso, 2021)
The pandemic context has become a critical test for policies guided by New Public Management (NPM). This perspective has promoted the outsourcing of the implementation of public policies and the installation of performance measurement instruments according to standards and results as a form of government of public action. Considering that Chile has been identified as an emblematic case of the installation of this type of policies, this study analyzed the performance and effects of these policies on the organization of work in two specific fields-education and protection policies for children and adolescents-, in the context of the COVID-19 Pandemic, based on the narrations of its workers. 40 interviews were conducted, which were analyzed from a discursive perspective. The results show that participants revealed a sense and organization of work aligned to what researchers have called the ethics of public work, denouncing the inappropriateness of the prescriptions of the NPM instruments. The actors reveal orientation to others and collaborative work under collectively constructed norms, as fundamental supports of a pertinent public action.
La ética de lo público y la impertinencia del managerialismo como modelo de organización del trabajo en tiempos de crisis
Keywords: Ethics of public work; New public management; Protection policies for children; Adolescentes; COVID-19; Education